Implementasi Server Log Monitoring System menggunakan Elastic Stack - Putu Napoleon Krishna Bayu (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Log monitoring system based on log management is a proposed method to monitor the state of a web server. This method is proposed because the logs generated by the server, can no longer be used to monitor the system state efficiently. This is due to the development of system scale that allows the placement of servers separately in several locations, each of which generates logs, so that its characteristics are similar to Big Data in log generation speed (speed), log storage size (volume), and variation in log structure (variation). Log management makes it easy for servers to be regularly managed and monitored. The log monitoring system using the Elastic Stack implemented on the Amazon Elastic Compute Cloud (EC2) trial environment worked well. By using the Elastic Stack, the log monitoring system successfully performs log management stages such as log collection, log transformation, log storage, and log analysis on logs generated by two separate web servers via a load testing of HTTP request, so that information from the logs can be processed and visualized through the monitoring dashboard on the log monitoring system.